2019
DOI: 10.1002/celc.201901151
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric H/D Isotope Effects on Redox‐Active Small Molecules Conjugated with DNA Self‐Assembled Monolayers

Abstract: This paper describes the largest H/D kinetic isotope effect (KIE) at room temperature (25 °C) reported to date (kH/kD=2400). In voltammetric measurements with DNA monolayers on gold electrodes, a maximum shift of −400 mV was recorded for the reduction peak potential of 50 μM hexammine cobalt(III) (CoHex) in 10 mM Tris buffer upon replacing water with deuterium oxide in the electrolyte. In subsequent comparative investigations, a much smaller shift (ca. −80 mV) was recorded with daunomycin, whereas no potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…Electrodes containing carbon material, such as glass carbon electrode (GCE), [14] have been used to analyze the electrochemical behavior of the reduction and oxidation of G and A on DNA strand. [27][28][29] Chen [30] and Gu [31] et al have demonstrated that the PGCE has obvious current response, good reproducibility and high stability, which can be used for studying thermal denaturation and acid denaturation dsDNA into ssDNA by cyclic voltammetry (CV) at PGCE. According to our previous study, we have not only achieved the simultaneous acquisition of the electrochemical signals of G and A at PGCE, but also realized the direct electron transfer of G in complex samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrodes containing carbon material, such as glass carbon electrode (GCE), [14] have been used to analyze the electrochemical behavior of the reduction and oxidation of G and A on DNA strand. [27][28][29] Chen [30] and Gu [31] et al have demonstrated that the PGCE has obvious current response, good reproducibility and high stability, which can be used for studying thermal denaturation and acid denaturation dsDNA into ssDNA by cyclic voltammetry (CV) at PGCE. According to our previous study, we have not only achieved the simultaneous acquisition of the electrochemical signals of G and A at PGCE, but also realized the direct electron transfer of G in complex samples.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical methods for the detection and analysis of DNA, purines and their derivatives have been developed rapidly. Electrodes containing carbon material, such as glass carbon electrode (GCE), [14] have been used to analyze the electrochemical behavior of the reduction and oxidation of G and A on DNA strand [27–29] . Chen [30] and Gu [31] et al.…”
Section: Introductionmentioning
confidence: 99%